2010
DOI: 10.1667/rr2203.1
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Decorporation of Americium by Pulmonary Administration of DTPA Dry Powder after Inhalation of Aged PuO2Containing Americium in Rats

Abstract: After inhalation of plutonium oxides containing various percentages of americium in rats, we identified an acellular transient pulmonary compartment, the epithelial lining fluid (ELF), in which a fraction of actinide oxides dissolve prior to absorption and subsequent extrapulmonary deposit. Chelation therapy is usually considered to be poorly efficient after inhalation of actinide oxides. However, in the present study, prompt pulmonary administration of diethylenetraminepentaacetic acid (DTPA) as a dry powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
2
16
0
1
Order By: Relevance
“…whole lung level. According to the ICRP, 0.1% of a type S compound is absorbed with a half-time of 10 min (2) and in our previous study, approximately 1% was absorbed by two weeks after inhalation of aged PuO 2 containing 5.2% of americium in activity (18).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…whole lung level. According to the ICRP, 0.1% of a type S compound is absorbed with a half-time of 10 min (2) and in our previous study, approximately 1% was absorbed by two weeks after inhalation of aged PuO 2 containing 5.2% of americium in activity (18).…”
Section: Discussionmentioning
confidence: 82%
“…In a previous study, we demonstrated the efficacy of local and prompt delivery of DTPA formulated as a dry powder after inhalation of PuO 2 , which was illustrated by the reduction of actinide extrapulmonary deposits (18). Although no decrease in pulmonary retention was obtained, a decrease in the level of activity associated with epithelial lining fluid (ELF) was observed.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Observed skeletal decorporation is likely due to removing plutonium from other organs and tissues. Depending on treatment protocol, DTPA administered by multiple daily treatments, intramuscular injection or nebulizer was proven to be more effective than by a single intravenous injection due to DTPA having a short residence time once it reaches the blood stream with a clearance half-time of 20 min (Durbin and Schmidt 1989;Gremy et al 2010Gremy et al , 2012Stather et al 1983;Volf 1974). The Ca-DTPA complex is initially more effective than Zn-DTPA for chelating plutonium, but due to the toxicity of Ca-DTPA, continued use is discouraged after the initial treatment (Durbin et al 1998;Gemenetzis and Volf 1977;IAEA 1978).…”
Section: Chelationmentioning
confidence: 99%